Cyclic guanosine monophosphate and 10-year change in left ventricular mass: the Multi-Ethnic Study of Atherosclerosis (MESA). (19th May 2021) - Subramanya, Vinita; Zhao, Di; Ouyang, Pamela; Ying, Wendy; Vaidya, Dhananjay; Ndumele, Chiadi E.; Lima, Joao A.; Guallar, Eliseo; Hoogeveen, Ron C.; Shah, Sanjiv J.; Heckbert, Susan R.; Kass, David A.; et al.
Abstract: Purpose: Cyclic guanosine monophosphate (cGMP) is a second messenger for natriuretic peptide (NP) and nitric oxide pathways; its enhancement a target for heart failure and cardiovascular disease (CVD). We evaluated whether plasma cGMP was associated with change in left ventricular mass (LVM) among individuals free of CVD and if this differed by sex. Methods and Results: In 611 men and 612 women aged 45–84 years with plasma cGMP measured at baseline and cardiac MRI performed at baseline and 10 years later, we tested associations of cGMP [log-transformed, per 1 SD increment] with LVM, adjusting for CVD risk factors and N-terminal pro-B-type-NP (NT-proBNP). Participants had mean (SD) age of 63.1(8.5) years and cGMP 4.8(2.6) pmol/mL. Cross-sectionally, higher cGMP was associated with lesser LVM, non-lin- early. In contrast, longitudinally, higher cGMP was associated with increase in LVM [1.70g (0.61, 2.78)] over 10 years. Higher cGMP was associated with greater LVM change in men [2.68g (1.57, 3.79)] but not women [0.24g ((−0.92, 1.39); p-interaction < 0.001]. Conclusion: In conclusion, in a community-based cohort, higher cGMP levels were associated with increase in LVM over 10 years independent of CVD risk factors and NT-proBNP in men, perhaps reflecting compensatory changes. Further studies are needed to understand mechanistic roles of cGMP in LV remodelling and associated sex differences.